Pemberdayaan Masyarakat Peduli Hipertensi sebagai Upaya Penurunan Tekanan Darah melalui Terapi Komplementer Slow Stroke Back Massage di Puskesmas 23 Ilir Palembang - Utama, Yofa Anggriani (Universitas Baiturrahim, 2025)
Until now hypertension is still on of the main causes of death in Indonesia and throughout the world. Hypertension is a non- communicable disease that often occurs in the elderly. Management of hypertension cases can be carried out by health workers and the community through the application of complementary therapies that can be utilized by community the aim of carrying out this community service activity is carried out in the work area of the 23 ilir Palembang health center on 28 – 31 july 2024, the activity was attended by 20 people suffering from hypertension in the working area of the 23 ilir Palembang health center.The results of the implementasi evaluation using a questionnaire showed that knowledge before health education obtained a mean value of 45,5. After being given health education there was an increase in knowledge with an average value of 75,5, so that a difference of 30 obtained, the participants skill before carrying out the simulation of Complementary Therapy Slow Stroke Back Massage therapy obtained an average value of 34, the participants skill after carrying out the simulation obtained an average of 76, so that a difference of 42.